Students’ Perception in Using Youtube to Learn English Speaking Autonomously - Muti'a M; Radiah Hamid; Syamsiarna Nappu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to find out what are students' perceptions in using YouTube to learn English speaking autonomously. This study used a qualitative design focused on students’ perception in using YouTube to learn English speaking components autonomously. This study used an open-ended questionnaire to collect data on students’ in using YouTube to learn English speaking components autonomously. The findings showed that the use of YouTube helps students to learn autonomously about English speaking components namely, pronunciation, vocabulary, and grammar, but not helpful for fluency. This research can be a reference for teachers /lecturers in making speaking materials needed by students, especially those who have an autonomous learning style.